2021
DOI: 10.1177/20587384211015034
|View full text |Cite
|
Sign up to set email alerts
|

Adipokine role in physiopathology of inflammatory and degenerative musculoskeletal diseases

Abstract: We performed a systematic literature review to summarize the underlying pathogenic mechanisms by which adipokines influence rheumatological diseases and the resulting clinical manifestations. Increasing evidence display that numerous adipokines may significantly influence the development or clinical course of various rheumatological diseases. Despite the normal anti- or pro-inflammatory role of the cytokines, the serum level varies enormously in various rheumatological diseases. The expression of high levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 139 publications
0
13
0
Order By: Relevance
“…and cytokines [interleukin (IL)-1, IL-6, IL-8, tumor necrosis factor (TNF)-α, etc. ], and contribute to the degeneration of chondrocyte and breakdown of extracellular matrix ( Urban and Little, 2018 ; Giardullo et al, 2021 ). The synovial adipokines might come from the secretion of the infrapatellar fat pad itself or from the blood circulation system permeating the synovial membrane and entering the joint cavity.…”
Section: Introductionmentioning
confidence: 99%
“…and cytokines [interleukin (IL)-1, IL-6, IL-8, tumor necrosis factor (TNF)-α, etc. ], and contribute to the degeneration of chondrocyte and breakdown of extracellular matrix ( Urban and Little, 2018 ; Giardullo et al, 2021 ). The synovial adipokines might come from the secretion of the infrapatellar fat pad itself or from the blood circulation system permeating the synovial membrane and entering the joint cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Several biomarkers of disease activity have been proposed in these patients, of them the most used are C-reactive protein (CRP) or erythrocyte sedimentation rate (ESR) included in most indices of disease activity, including the Disease Activity Score of 28 Joints (DAS28) [3,5]. Recently, some adipokines were found to be involved in several inflammatory processes lead by the immune system [6]. Among these adipokines, chemerin has been identified as a molecule implicated in the inflammation mediated by immune mechanisms [7].…”
Section: Introductionmentioning
confidence: 99%
“…The third factor is that increased BFP and enlarged fat cells cause sarcopenic obesity and promote chronic inflammation and insulin resistance. One study showed that apelin secreted by fat cells also regulates bone turnover and lowers BMD, increasing catabolism and leading to sarcopenia ( 39 ). Regardless of the underlying mechanisms, from a clinical perspective the most effective and appropriate strategy to prevent osteoporosis-related fractures is lifestyle modification (e.g., exercise and nutrition).…”
Section: Discussionmentioning
confidence: 99%